Specialized ducational care in the development of the student with autism (Research, Society and Development, 2023)
The Specialized Educational Service - AEE is ensured by law through the Multifunctional Resource Rooms - SRM through federal resolution, to meet students with different disabilities, in a complementary and supplementary way, which includes neurodevelopmental disorder, where the Autism Spectrum Disorder - ASD is located. Aiming to contribute and participate in the process of inclusion of the student with autism, the teacher of the Specialized Educational Service has different and arduous functions within the school environment, which go through the limits of the school. This teacher of the special education modality should articulate intersectoral dialogues in favor of the students, involving therapists, clinicians, family and other care. This article shows, through the field research, carried out in the municipality of Itaboraí/RJ, in 2019, the time of work and the academic training of the professionals who make up the special education, being these those who work in the Multifunctional Resource Rooms, and those who perform the school mediation, assisting the students with autism. In this, through the answers of the interviewees, it is possible to evidence the need and importance of qualification and specific complementary training, taking into account the aspects that make up the disorder and the specificities of each individual within the spectrum.